Answer:
18. x = y = -3
21. y was substituted into the wrong equation. The solution is (x, y) = (2, 1).
Explanation:
18. Adding y to the first equation transforms it to ...
... x = y
Then you can substitute for either variable in the second equation.
... 2y -5y = 9 . . . . . substitute for x
... -3y = 9 . . . . . . . . simplify
... y = -3 . . . . . . . . . divide by the coefficient of y
.. x = -3 . . . . . . . . . x and y have the same value
___
21. The first equation is being used to find an expression for y in terms of x. If you substitute that expression back into the same equation, it will tell you nothing you didn't already know. (Here, it is telling you 5 = 5.) The expression is only useful if you substitute it into a different equation. Here, it needs to be substituted into the second equation:
... Step 2: 3x -2(-2x+5) = 4 ⇒ 7x -10 = 4 . . . . . substitute for y in the second eqn
... Step 3: 7x = 14 . . . . . add 10
... Step 4: x = 2 . . . . . . . divide by 7
... Step 5: y = -2·2 +5 = 1 . . . . . find the value of y from x using the expression from step 1. Now, you know the solution is (x, y) = (2, 1).
_____
The attached graph shows the solution to the problem of 21.